Study on characteristic, genetic variation of pC8B complement molecule and its potential source for improving disease resistance in pig - Khoa, Đỗ Võ Anh; Wimmers, Klaus (Vietnam Journal of Biotechnology, 2012)
The aim of study was to analyze structure, function and genetic characteristics of the porcine C8B complement gene (pC8B) forward to selecting immune valuable genotypes for health improvement in pig. Sequencing and PCR-RFLP methods were used to identify cDNA sequence and to evaluate genotypic frequency of the locus pC8B, respectively. As result, the pC8B macromolecule physically located on the chromosome 6q3.3-3.5 has a cDNA sequence of 1987 nucleotides encoding 611 amino acids. A single nucleotide polymorphism at position 1244AàG agreeing with Hardy-Weinberg equilibrium was detected between European breeds and Muong Khuong. It seems to be the pC8B was mosaic protein constructed from smaller immune rich-cysteine protein segments such as TSP1 (thrombospondin-1), LDLa (lipoprotein A), MACPF (membrane-attack complex/perforin), and EGF (epidermal growth factor). The results, therefore, promote the pC8B as a greatly potential candidate gene for natural defence system of host body against invading pathogens.